Extranodal lymphoma masquerading as carcinoma of the breast in an HIV-positive male patient - Rastogi, Madhup (BMJ Case Rep, 2012)
This report describes a male patient infected with the HIV, with antiretroviral therapy (ART)-induced gynaecomastia. He presented with a right-sided breast mass which clinically resembled a carcinoma. A core biopsy suggested non-Hodgkin's lymphoma of diffuse large B cell histology. Also presented are his 18-fluoro-deoxy-glucose - positron emission tomography (FDG PET)-CT scan findings which showed a highly avid mass (standardised uptake value (SUV) 34.5) in his right breast. In spite of a very good clinical response after the first cycle of chemotherapy, his disease relapsed at multiple sites and progressed early. This case illustrates the aggressive course of HIV-associated extranodal lymphomas, and also highlights the issues concerning the use of ART and chemotherapy.